GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

 It is currently 26 May 2020, 20:09

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 64144
If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f  [#permalink]

### Show Tags

02 Apr 2020, 10:02
00:00

Difficulty:

25% (medium)

Question Stats:

90% (02:05) correct 10% (03:32) wrong based on 20 sessions

### HideShow timer Statistics

If $$f(x) = \frac{5x+2}{3x−5}$$ and $$g(x) = x^2 – 2x – 1$$, then the value of $$g(f(f(3)))$$ is:

A. 1/3
B. 2/3
C. 1
D. 2
E. 6

_________________
Senior Manager
Joined: 12 Dec 2015
Posts: 492
Re: If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f  [#permalink]

### Show Tags

02 Apr 2020, 10:18
If $$f(x) = \frac{5x+2}{3x−5}$$ and $$g(x) = x^2 – 2x – 1$$, then the value of $$g(f(f(3)))$$ is:

A. 1/3
B. 2/3
C. 1
D. 2 --> correct: f(3)=$$\frac{5*3+2}{3*3−5}$$ = $$\frac{17}{4}$$, f(f(3))=f(17/4)=$$(5*(17/4)+2)/(3*(17/4)−5)$$ =$$\frac{85+8}{51−20}$$ =$$\frac{93}{31}$$ = 3, so g(f(f(3))) = g(f(17/4)) = g(3) = 3^2-2*3-1=9-6-1=2
E. 6
Senior Manager
Status: Today a Reader; Tomorrow a Leader.
Joined: 14 Oct 2019
Posts: 404
Location: India
GPA: 4
WE: Engineering (Energy and Utilities)
Re: If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f  [#permalink]

### Show Tags

02 Apr 2020, 10:22
f(x)=5x+2/3x−5 and g(x)=x2–2x–1
f(3)=(5*3+2)/(3*3−5) = 17/4
now, f(17/4) =(5*17/4+2)/(3*17/4−5) = 73/31 = 3
therefore, g(f(f(3))) = g(3) =3^2–2*3–1 = 2

correct answer is D
Re: If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f   [#permalink] 02 Apr 2020, 10:22

# If f(x) = (5x+2)/(3x−5) and g(x) = x^2 – 2x – 1, then the value of g(f

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne